Numbered Heads Together Cooperative Learning in Learning Collaboration and Communication Skills Based on Lesson Study Activities - Bella, Beartrix; Istikomayanti, Yuswa; Lathifah, Anis Samrotul (Tarbiyah : Jurnal Ilmiah Kependidikan, 2024)
Education directly continues to experience a process of change from time to time. In 21st-century learning, there are important skills for students, namely collaboration and communication skills. This research aims to discover how students' collaboration and communication skills apply the NHT learning model to excretory system material. This lesson study activity consists of 2 meetings; the implementation stages are plan, do, and see. The planning stage is on May 14, 2023, for the first and second meetings; the do stage is on May 23, 2023, for the first meeting and May 25, for the second meeting. View stage: May 23, First meeting, and May 26, second meeting. The subjects in this research were 17 class VIII students at Sunan Giri Middle School, Malang. The instruments used are observation sheets, reflection notes, and documentation. The results show student collaboration and communication skills change during the first and second meetings. Meanwhile, N-Gain's overall score for collaboration skills is 0.43 in the medium category, and communication skills is 0.40 in the medium category. In this research, collaboration skills are more prominent than communication skills.  NHT is quite relevant for increasing student collaboration and also student competition between groups.